Resveratrol as a Chemopreventive Agent in Lung Cancer Therapy - Fransisca Dela Verna (HM Publisher, 2022)
For decades, lung cancer has been the most widespread cancer in the world and the leading cause of cancer death. Lung malignancy is the superior cause of death in Indonesia, accompanying the second topmost number of new cases. The low survival rate of lung cancer patients reflects the therapy's low success rate due to side effects and cancer cells' resistance to chemotherapy and radiotherapy. Combination therapy, which includes the use of chemopreventive agents, can reduce the risk of side effects and resistance. Natural product-based chemopreventive agents used together with accompanying chemical anti-cancer drugs and/or actinotherapy can overcome cancer cell resistance, improve therapy effectiveness, and reduce side effects. Resveratrol is a compound belonging to the non-flavonoid polyphenolic group contained, particularly in vine fruits, berries, and some nuts. Resveratrol exhibits anti-cancer activity, according to considerable in vitro and in vivo studies, and hence has what it takes to be reasonably applied as a chemopreventive compound. The discovery of resveratrol's chemopreventive mechanism against lung cancer is expected to enable the development of a chemopreventive compound that can be used together with accompanying chemical anti-cancer drugs and/or actinotherapy.